(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objectives of this study were to determine the hatchingtraits, brooding growth performance and mortality of turkey (Meleagrisgallopavo) poults under Sudan conditions. Six hundred fertile eggs werebrought from France and hatched in Khartoum during March 8 to April 62011 and poult brooding was conducted at the University of Bahri Farmfrom April 6 to May 4 2011. The results showed that turkey egg had98.83 % fertility, 79.26 % hatchability of total eggs, 80.2 % hatchabilityof fertile eggs, 61.9 % of first class poults from total eggs incubated, 77 %first class poults from eggs hatched. Poults weighed 49.52 100.02, 183.78,332.18 and 548.84 g at one day old and at the end of weeks, 1, 2, 3 and 4,respectively. Mortality was 7.37 % and 100 % for first and second classpoults, respectively. This is the first study done on turkey under Sudanconditions. It is hoped that this study may be a pioneer to invite more indepth research on turkey specially now when poultry industry is booming.